Response of Chloroplast NAD(P)H Dehydrogenase-Mediated Cyclic Electron Flow to a Shortage or Lack in Ferredoxin-Quinone Oxidoreductase-Dependent Pathway in Rice Following Short-Term Heat Stress - Essemine, Jemaa; Qu, Mingnan; Mi, Hualing; Zhu, Xin-Guang (Frontiers in Plant Science, 2016)
Cyclic electron flow around PSI can protect photosynthetic electron carriers under conditions of stromal over-reduction. The goal of the research reported in this paper was to investigate the responses of both PSI and PSII to a short-term heat stress in two rice lines with different capacities of cyclic electron transfer, i.e. Q4149 with a high capacity (hcef) and C4023 with a low capacity (lcef). The absorbance change at 820 nm (ΔA820) was used here to assess the charge separation in the photosystem I (PSI) reaction center (P700). The results obtained show that short-term heat stress abolishes the FQR-dependent CEF in rice and accelerates the initial rate of P700+ re-reduction. The P700+ amplitude was slightly increased at a moderate heat-stress (35°C) because of a partial restriction of FQR but it was decreased following high heat-stress (42°C). Assessment of PSI and PSII activities shows that PSI is more susceptible to heat stress than photosystem II (PSII). Under high temperature, FQR-dependent CEF was completely removed and NDH-dependent CEF was up-regulated and strengthened to a higher extent in C4023 than in Q4149. Specifically, under normal growth temperature, hcef (Q4149) was characterized by higher FQR- and NDH-dependent CEF rates than lcef (C4023). Following thermal stress, the activation of NDH-pathway was 130% and 10% for C4023 and Q4149, respectively. Thus, the NDH-dependent CEF may constitute the second layer of plant protection and defence against heat stress after the main route, i.e. FQR-dependent CEF, reaches its capacity. We discuss the possibility that under high heat stress, the NDH pathway serves as a safety valve to dissipate excess energy by cyclic photophosphorylation and overcome the stroma over-reduction following inhibition of CO2 assimilation and any shortage or lack in the FQR pathway. The potential role of the NDH-dependent pathway during the evolution of C4 photosynthesis is briefly discussed.